Dispersed Ru nanoclusters transformed from a grafted trinuclear Ru complex on SiO2for selective alcohol oxidation - Satoshi Muratsugu (2018)
Ru nanoclusters (average diameter = 1.3 ± 0.3 nm) were successfully prepared by using a Ru3cluster Ru3O(CH3COO)6(H2O)3·(CH3COO) grafted on a pyridine-functionalized SiO2surface. The pyridine moiety dispersed on the SiO2surface spread the Ru3cluster, controlling its surface density, and the nanoclusterization of the Ru cluster proceeded on the surface. The structures of the Ru nanoclusters were characterized by means of elemental analysis; thermogravimetric analysis; FT-IR, UV/vis, and solid-state NMR spectroscopy; BET analysis; X-ray photoelectron spectroscopy; X-ray diffraction; transmission electron microscopy; and Ru K-edge X-ray absorption fine structure analysis. It was found that the catalytic activity for the selective oxidation of alcohol to the corresponding aldehyde using O2highly depended on the dispersion and structures of the Ru particles, and the Ru nanocluster was found to be efficient in the selective oxidation of a variety of alcohols. © 2013 The Royal Society of Chemistry.